Hormesis and Low Toxic Effects of Three Lanthanides in Microfungi Isolated from Rare Earth Mining Waste in Northwestern Russia - Elena A. Kasatkina; Oleg I. Shumilov; Irina Y. Kirtsideli; Dmitry V. Makarov (Toxics, 2023)
The low-dose toxicity of chloride and nitrate salts of three lanthanides (La, Ce and Nd) was tested on six microfungal species. Five of them ( Geomyces vinaceus , Aspergillus niveoglaucus , Pseudogymnoascus pannorum , Penicillium simplicissimum and Umbelopsis isabellina ) were isolated from the loparite ore tailings on the Kola Peninsula, northwestern Russia. Sydowia polyspora was a control strain. In the case of nitrate salts, the toxicity of REEs to four of six microorganisms was significantly ( p < 0.5) lower compared to chloride salts. In this case, nitrates can play the role of exogenous nutrients, compensating for the toxic effect of REEs. Interestingly, U. isabellina only showed an opposite response, indicating the highest toxicity of nitrate (IC 5 = 9–20 mg/L) REEs’ salts compared to chlorides (IC 5 = 80–195 mg/L) at low concentration levels. In addition, treatment with lanthanides showed a “hormesis effect” on fungal growth with stimulation at low doses and inhibition at high doses. However, U. isabellina and S. polyspora demonstrated the absence of hormetic response under the treatment of REEs’ nitrate salt. Taking into account the specific hormetic responses and high tolerance of P. simplicissimum and U. isabellina to lanthanides, our findings may be useful in the assessment of the potential application of the selected fungi to bioremediation and REE bioleaching.